Phone-based Intervention under Nurse Guidance after Stroke (PINGS): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Sarfo, Fred; Treiber, Frank; Jenkins, Carolyn; Patel, Sachin; Gebregziabher, Mulugeta; Singh, Arti; Sarfo-Kantanka, Osei; Saulson, Raelle; Appiah, Lambert; Oparebea, Eunice; Ovbiagele, Bruce
Abstract Background Hypertension is the premier modifiable risk factor for recurrent stroke. In sub-Saharan Africa (SSA) where the stroke burden is escalating, little is known about the role of behavioral interventions in enhancing blood pressure (BP) control after stroke. Our objective is to test whether an m-Health technology-enabled, nurse-led, multilevel integrated approach is effective in improving BP control among Ghanaian stroke patients within 1 month of symptom onset compared with standard of care. Methods This two-arm cluster randomized controlled feasibility pilot trial will involve 60 recent-stroke survivors. Using a computer-generated sequence, patients will be randomly allocated into four clusters of 15 patients each per physician: two clusters in the intervention arm and two in the control arm. Patients in the intervention arm will receive a simple pillbox, a Blue-toothed UA-767Plus BT BP device and smartphone for monitoring and reporting BP measurements and medication intake under nurse guidance for 3 months. Tailored motivational text messages will be delivered based upon levels of adherence to the medication intake. Both groups will be followed up for 6 months to compare BP control at months 3, 6 and 9 as primary outcome measure. Physicians assessing BP control will be blinded to arms into which patients are allocated. Secondary outcome measures will include medication adherence scores and Competence and Autonomous Self-regulation Scale scores. A qualitative study is planned after follow-up to explore the lived experiences of participants in the intervention arm. Discussion A feasible and preliminarily effective intervention would lead to a larger more definitive efficacy/effectiveness randomized controlled trial powered to look at clinical events, with the potential to reduce stroke-related morbidity and mortality in a low- to middle-income country. Trial registration ClinicalTrials.gov Identifier:NCT02568137, registered on 13 July 2015.